Continuance Adoption of Online Stock Trading Among Investors of Kathmandu Valley - Pokhrel, Laxman; Sapkota, Sunita (Nepalese Journal of Insurance and Social Security, 2024)
Purpose: This paper investigates the continuance adoption of online stock trading among investors in Kathmandu Valley. Methodology: Using self-administered questionnaires, this paper applied a purposive sampling technique to collect data from 271 stock investors in the Kathmandu Valley. Structural Equation Modeling (SEM) was used to estimate proposed model. Findings and Conclusions: This paper found that satisfaction, habit, and disconfirmation have significant positive influence on the adoption of online stock trading among investors in the Kathmandu Valley. However, perceived usefulness, subjective norms, and continuance intention do not appear to have any significant influence on the adoption of online stock trading among investors in the Kathmandu Valley. The result implies that 70% of variance of continuance behavior is explained by the existing model. Implications: This paper has theoretical and managerial implications. Theoretically, this paper studies continuance adoption of online stock trading in Nepali context and found investors in Nepal continue adopt online stock trading if they perceive it to be easy, satisfying, useful, and habitual investors continue adopting online stock trading. Managerially, this paper could provide empirical evidence to design promotional strategies of online stock trading for SEBON (Securities Board of Nepal) to increase awareness level among online stock investors.